Analysis of the Influence of Financial Performance on the Value of Sharia Banking Companies in Indonesia - Rokhimah, Zulaika Putri; Eviyanti, Novitasari; Senoaji, Aditya Rizqi (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to test and analyze the influence of financing to deposit ratio (FDR), capital adequacy ratio (CAR), return on assets (ROA), non-performing financing (NPF), operating expenses and operating income (BOPO) on firm value (PBV). . This research was conducted on Sharia Banking in 2019-2021. This research is quantitative research and uses secondary data taken through financial reports taken by purposive sampling. The samples obtained were 33 data. The data analysis method was carried out using the SPSS program. The analytical tool used in this research is multiple linear regression analysis. The research results show that FDR, ROA and BOPO have a negative effect on company value, while CAR and NPF have a positive effect on company value.